2019
DOI: 10.1111/are.14018
|View full text |Cite
|
Sign up to set email alerts
|

Length–weight relationship and growth performance of different life stages of hatchery‐produced magur,Clarias magur(Hamilton, 1822)

Abstract: Length–weight relationship (LWR) of 661 numbers of hatchery‐produced magur, Clarias magur of all the life stages such as hatchlings, fry, fingerlings, juveniles and adults, was studied. The LWR of all the life stages of magur was estimated and the equations are as follows, hatchlings W = 0.0052*L1.282 (r2 = 0.8784), fry W = 0.0088*L3.028 (r2 = 0.8113), fingerlings W = 0.0065*L3.226 (r2 = 0.8906), juveniles W = 0.0028*L3.420 (r2 = 0.8175) and adults W = 0.0017*L3.491 (r2 = 0.8310). A positive allometric growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
(46 reference statements)
1
2
0
Order By: Relevance
“…In the present study, a negative allometric growth (b ˂ 3) was observed in all sorts of feed, indicating an elongated body shape of the fish with a lesser width (Froese, 2006). The b value reported in this study is similar to that reported previously from the same species (2.6 for males and 2.8 for females) (Mia, 1984) as well as from other catfishes, including C. batrachus (1.282) (Sahoo et al, 2019) and C. gariepinus (2.9 for female and 2.74 for male) (Yalcin et al, 2002). Among the four feeds tested in the present study, dry Tubifex produced a b value lower than the limit (2-4) (Tesch, 1971) suggesting inappropriate choice as an alternative to live foods.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, a negative allometric growth (b ˂ 3) was observed in all sorts of feed, indicating an elongated body shape of the fish with a lesser width (Froese, 2006). The b value reported in this study is similar to that reported previously from the same species (2.6 for males and 2.8 for females) (Mia, 1984) as well as from other catfishes, including C. batrachus (1.282) (Sahoo et al, 2019) and C. gariepinus (2.9 for female and 2.74 for male) (Yalcin et al, 2002). Among the four feeds tested in the present study, dry Tubifex produced a b value lower than the limit (2-4) (Tesch, 1971) suggesting inappropriate choice as an alternative to live foods.…”
Section: Discussionsupporting
confidence: 90%
“…The domestication of fish species for commercial aquaculture is essential to the development of the industry. The Asian catfish, Clarias magur, is highly demanded in the markets of the Indian subcontinent, and it is considered to be an important alternative species for species diversification in India and other Asian countries (Areerat, 1987;Sahoo et al, ,2016Sahoo et al, , , 2019. C. magur has a great potential for species diversification projects due to the possibility for high-density rearing, since the catfish is an air-breathing species able to thrive in low dissolved oxygen environment, has therapeutic benefits, high nutritional profile made up of easily digestible proteins and high iron content in the muscle (Argungu et al, 2013;Debnath, 2011;Hossain et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The domestication of fish species for commercial aquaculture is essential to the development of the industry. The Asian catfish, Clarias magur , is highly demanded in the markets of the Indian subcontinent, and it is considered to be an important alternative species for species diversification in India and other Asian countries (Areerat, 1987; Sahoo et al, ,2016, 2019). C .…”
Section: Introductionmentioning
confidence: 99%